2021
DOI: 10.7554/elife.60005
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of neural crest lineages along the posterior developing zebrafish at single-cell resolution

Abstract: Neural crest cells (NCCs) are vertebrate stem cells that give rise to various cell types throughout the developing body in early life. Here, we utilized single-cell transcriptomic analyses to delineate NCC-derivatives along the posterior developing vertebrate, zebrafish, during the late embryonic to early larval stage, a period when NCCs are actively differentiating into distinct cellular lineages. We identified several major NCC/NCC-derived cell-types including mesenchyme, neural crest, neural, neuronal, glia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 146 publications
13
88
0
Order By: Relevance
“…Firstly, our use of NanoString technology and a refined RNAscope protocol has given increased sensitivity to low level gene expression. For example, expression of ltk in the progenitor cells in this study is rather variable, reflecting the notably low levels of WISH expression in the ‘early’ phases 1315 , and consistent with the absence of ltk as a marker in recent scRNA-seq studies 61,62 . Our recent expanded WISH characterization identified co-expression with ltk of sox10, tfec and mitfa as characteristic of the putative chromatoblast (MIX) 13,14 , and we see these genes as more robust components of the ltHMP progenitor identified by our single cell transcriptional profiling here.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Firstly, our use of NanoString technology and a refined RNAscope protocol has given increased sensitivity to low level gene expression. For example, expression of ltk in the progenitor cells in this study is rather variable, reflecting the notably low levels of WISH expression in the ‘early’ phases 1315 , and consistent with the absence of ltk as a marker in recent scRNA-seq studies 61,62 . Our recent expanded WISH characterization identified co-expression with ltk of sox10, tfec and mitfa as characteristic of the putative chromatoblast (MIX) 13,14 , and we see these genes as more robust components of the ltHMP progenitor identified by our single cell transcriptional profiling here.…”
Section: Discussionsupporting
confidence: 88%
“…We reconcile our new view of NCCS retaining high multipotency with the more conventional observations interpreted under a PFR model in former studies (e.g. 13,14,23,61,62 ) by noting technical differences in our approaches. Firstly, our use of NanoString technology and a refined RNAscope protocol has given increased sensitivity to low level gene expression.…”
Section: Discussionsupporting
confidence: 82%
“…They include an atlas of neural crest lineages [ 50 ], two different studies of using whole embryo single-cell analysis during the first day of zebrafish development [ 10 , 11 ], a single-cell transcriptome atlas for zebrafish at 1, 2 and 5 dpf stages [ 9 ] and others. Previous studies have either focused on specific tissues or cell populations such as neural crest or vascular endothelial progenitors [ 31 , 50 ], or have performed analysis at embryonic stages which are different from our study. A recent study has reported a single-cell transcriptome atlas for zebrafish at 1, 2 and 5 dpf stages [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the power and flexibility of the WICHCR protocol, we went on to analyze 5 markers simultaneously. Relying on our expertise in neural crest stem cell biology to guide which probes to examine, we have employed antibodies against Sox10, which labels migrating neural crest cells (NCC) ( Carney et al., 2006 ), and phosphorylated Histone H3 (pHH3) , a canonical marker for cell division ( Kim et al., 2017 ), as well as HCR probe sets against barx1 , mitfa , and sox10 , labeling mesenchyme, melanophore/pigment progenitors, and NCC respectively ( Howard et al., 2021 ) ( Figure 2 ). Following the WICHCR protocol, confocal images were spectrally deconvolved, distinguishing the signals in the corresponding wavelength for each of the fluorescent markers used ( Figures 2 A–2F).…”
Section: Expected Outcomesmentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Choi et al. (2010 , 2016 , 2018) and Howard et al. (2021) .…”
mentioning
confidence: 99%